2019
DOI: 10.1177/1540796919826229
|View full text |Cite
|
Sign up to set email alerts
|

Parent Experiences of Raising a Young Child with Multiple Disabilities: The Transition to Preschool

Abstract: Families raising young children diagnosed with multiple disabilities encounter experiences that are often unique and extend well beyond the early childhood years due to the intensity and severity of their child's needs. The contexts of these families must be understood to provide meaningful services and supports, particularly during the child's transition from early intervention to preschool services. In this transcendental phenomenological inquiry, 10 parents of young children with multiple disabilities who t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 27 publications
(72 reference statements)
2
33
0
Order By: Relevance
“…Findings revealed that many factors across interacting systems act as facilitators or barriers to successful intervention implementation and outcomes for students with complex communication needs. The factors stakeholders discussed were largely consistent with prior knowledge of ecological systems (Bronfenbrenner, 1979), expanding existing research to strengthen understanding about how students with complex communication needs function within a set of nested systems (Lindsay et al, 2015;Mandak et al, 2017;Odom et al, 2004;Waters & Friesen, 2019). The factors and interactions across ecological systems can have rippling and important impacts both on AAC implementation and on outcomes more broadly for this group of students.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Findings revealed that many factors across interacting systems act as facilitators or barriers to successful intervention implementation and outcomes for students with complex communication needs. The factors stakeholders discussed were largely consistent with prior knowledge of ecological systems (Bronfenbrenner, 1979), expanding existing research to strengthen understanding about how students with complex communication needs function within a set of nested systems (Lindsay et al, 2015;Mandak et al, 2017;Odom et al, 2004;Waters & Friesen, 2019). The factors and interactions across ecological systems can have rippling and important impacts both on AAC implementation and on outcomes more broadly for this group of students.…”
Section: Discussionmentioning
confidence: 53%
“…For example, Odom et al (2004) used a conceptual framework based on ecological systems to review research on the inclusion of young children with disabilities, discussing factors such as teacher attitudes, classroom practices, and classroom quality (microsystem); family-school interactions (mesosystem); policies and administrative issues (exosystem); and the broader culture (macrosystem). Waters and Friesen (2019) used an ecological perspective to explore the experiences of families of young children with multiple disabilities transitioning into preschool services. Their findings provided insight into the importance of broader systems of support for families (e.g., familial supports, other parents of children with disabilities).…”
mentioning
confidence: 99%
“…The priority of their youth's high health and medical needs made it challenging to adjust their parenting to encourage greater opportunities for youth to develop their life skills. Changes in the interaction and development of family members (family functioning), in addition to changes in the emotional bonding among family members (family cohesion), can prove to be complex and challenging for families with a disabled youth (Kingsnorth et al, 2019; Olson et al, 1979; Waters & Friesen, 2019). In particular, the multiple healthcare and community services a young person may require can also add to the impact on family functioning and cohesion (Olson et al, 1979; Waters & Friesen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the interaction and development of family members (family functioning), in addition to changes in the emotional bonding among family members (family cohesion), can prove to be complex and challenging for families with a disabled youth (Kingsnorth et al, 2019; Olson et al, 1979; Waters & Friesen, 2019). In particular, the multiple healthcare and community services a young person may require can also add to the impact on family functioning and cohesion (Olson et al, 1979; Waters & Friesen, 2019). We posit that when parents adjusted their parenting, it did in fact create opportunities for youth to develop their life skills further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation